A new egg ‒ mimic Passiflora species (Passifloraceae) from Huancabamba Province, Piura, Peru - Esquerre-Ibañez, Boris (2019)
Passiflora santos-llatasii is described and illustrated as a new species in Passiflora subgenus Decaloba (Passifloraceae). It is endemic to western cloud forests from the Huancabamba Province in Piura Department, in northern Peru. This species is similar to the Brazilian P. pardifolia, but differs mainly in leaves color, bracts size, flower corona –both in color and series number, fruit shape, and distribution of wild populations. Additional information about etymology, ecology, distribution and conservation is added, with discussion of similar species.